Risk Management in the Malaysian Build Operate Transfer Projects - Ahmad, Usman; Akram, Kashif; Fatima, Erum; Hussain, Muhammad (iRASD Journal of Economics, 2021)
In Malaysia, Public Private Partnership (PPP) is one of the tools to develop infrastructure. Although, there are various forms of PPP projects but Build Operate and Transfer (BOT) is commonly used in infrastructural projects. Despite, the benefits of adopting PPP, there are a few issues that require focus of the practitioners and researchers such as; risk management in PPP projects. Therefore, this study describes the process of risk management in Malaysian BOT Projects as this PPP arrangement is applied in infrastructure development. The study has employed the exploratory sequential research method to achieve the objective. The results of the study concludes that most of the extreme risks are allocated to SPV thus selection of SPV is crucial for BOT projects.